2023
DOI: 10.18240/ijo.2023.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 suppresses the hypoxia-induced angiogenesis of human retinal endothelial cells by targeting PlGF

et al.

Abstract: AIM: To investigate the anti-angiogenic effect of apolipoprotein A1 (apoA1) on primary human retinal vascular endothelial cells (HRECs) and explore the possible mechanism. METHODS: The primary HRECs were transfected with apoA1-GFP recombinant lentiviral and were compared with cells undergoing transfection with empty lentiviral vectors. Hypoxia chambers were used to simulate the anoxic environment of cells under pathological condition. The concentrations of secreted vascular endothelial growth factor (VEGF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hemoglobin subunit α, located at the myoendothelial junction of vessels, regulates endothelial nitric oxide synthase activity and nitric oxide diffusion 55 . Apolipoprotein A1 exhibits anti‐angiogenic activity by inactivating extracellular signal‐regulated kinase 1/2 in hypoxic tissue environments 56 . It also suppresses placental growth factor (PlGF), associated with pathological angiogenesis 56 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hemoglobin subunit α, located at the myoendothelial junction of vessels, regulates endothelial nitric oxide synthase activity and nitric oxide diffusion 55 . Apolipoprotein A1 exhibits anti‐angiogenic activity by inactivating extracellular signal‐regulated kinase 1/2 in hypoxic tissue environments 56 . It also suppresses placental growth factor (PlGF), associated with pathological angiogenesis 56 .…”
Section: Discussionmentioning
confidence: 99%
“… 55 Apolipoprotein A1 exhibits anti‐angiogenic activity by inactivating extracellular signal‐regulated kinase 1/2 in hypoxic tissue environments. 56 It also suppresses placental growth factor (PlGF), associated with pathological angiogenesis. 56 Apolipoprotein D similarly demonstrates anti‐angiogenic activity and plays a role in axon regeneration and remyelination for functional recovery of peripheral nerve integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apo1 has been suggested as promising novel biomarker for diagnosis of coronary artery disease 52 and it has been shown that ApoA1 is associated with pathological angiogenesis in hypoxia-induced human retinal vascular endothelial cells by inhibiting ERK1/2 signaling 53 .…”
Section: Discussionmentioning
confidence: 99%